2012
DOI: 10.1371/journal.pone.0032894
|View full text |Cite
|
Sign up to set email alerts
|

Statins but Not Aspirin Reduce Thrombotic Risk Assessed by Thrombin Generation in Diabetic Patients without Cardiovascular Events: The RATIONAL Trial

Abstract: BackgroundThe systematic use of aspirin and statins in patients with diabetes and no previous cardiovascular events is controversial. We sought to assess the effects of aspirin and statins on the thrombotic risk assessed by thrombin generation (TG) among patients with type II diabetes mellitus and no previous cardiovascular events.Methodology/Principal FindingsProspective, randomized, open, blinded to events evaluation, controlled, 2×2 factorial clinical trial including 30 patients randomly allocated to aspiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…In this randomized clinical trial (START), we have shown that treatment with rosuvastatin leads to a relative reduction in thrombin generation potential, decreasing the ETP by 10.4% (adjusted mean difference between treatments, −129.39 n m *min) and decreasing the thrombin peak by 5% (adjusted mean difference between treatments, −13.69 n m ), in comparison with non‐statin treatment. Our results confirm previous clinical studies that also demonstrated that statin therapy, either with rosuvastatin , simvastatin , atorvastatin or cerivastatin , affects coagulation factors and thrombin generation.…”
Section: Discussionsupporting
confidence: 92%
“…In this randomized clinical trial (START), we have shown that treatment with rosuvastatin leads to a relative reduction in thrombin generation potential, decreasing the ETP by 10.4% (adjusted mean difference between treatments, −129.39 n m *min) and decreasing the thrombin peak by 5% (adjusted mean difference between treatments, −13.69 n m ), in comparison with non‐statin treatment. Our results confirm previous clinical studies that also demonstrated that statin therapy, either with rosuvastatin , simvastatin , atorvastatin or cerivastatin , affects coagulation factors and thrombin generation.…”
Section: Discussionsupporting
confidence: 92%
“…For aspirin an effect in platelet poor plasma is not to be expected, although one recent report indicates a trend for accelerated thrombin formation in long-term aspirin users [13]. The use of statins might have attenuated thrombin generation in platelet poor plasma, as reported in several studies [14]–[16]. The fact that we did not observe any effects may have been due to the relatively low percentage of statin users in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…We chose atorvastatin because it was widely available as a generic compound (whereas rosuvastatin was a brand-name only compound during the time of study period). Moreover, atorvastatin had previously been shown to reduce thrombin generation in patients with cardiovascular disease or diabetes (28,31). Second, we started atorvastatin within 3 weeks of the index acute VTE, along with anticoagulation, instead of waiting until after patients had stopped anticoagulation.…”
Section: Discussionmentioning
confidence: 99%